2002
DOI: 10.1103/physrevlett.88.186401
|View full text |Cite
|
Sign up to set email alerts
|

Ultranonlocality in Time-Dependent Current-Density-Functional Theory: Application to Conjugated Polymers

Abstract: We solve the long-standing problem of the large overestimation of the static polarizability of conjugated polymers obtained using the local density approximation within density-functional theory. The local approximation is unable to describe the highly nonlocal exchange and correlation (xc) effects found in these quasi-one-dimensional systems. Time-dependent current-density-functional theory enables a local current description of ultranonlocal xc effects using the Vignale-Kohn functional [G. Vignale and W. Koh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
238
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(246 citation statements)
references
References 25 publications
(30 reference statements)
7
238
1
Order By: Relevance
“…As shown in ref 48, accurately predicting the polarizability of the H 2 linear chain is particularly difficult for semilocal functionals. Figure 2 presents the longitudinal polarizability per H 2 fragment for oligomers of various lengths and the periodic chain.…”
Section: Polarizabilities In H 2 Chainsmentioning
confidence: 99%
“…As shown in ref 48, accurately predicting the polarizability of the H 2 linear chain is particularly difficult for semilocal functionals. Figure 2 presents the longitudinal polarizability per H 2 fragment for oligomers of various lengths and the periodic chain.…”
Section: Polarizabilities In H 2 Chainsmentioning
confidence: 99%
“…It is found that the values of ␣ av DFPT for the two polymers are in reasonable agreement with typical data for the axial polarizability of conjugated polymers. 16,17 The calculated permittivity values of PPyV also show strong anisotropy, with ␤ zz ӷ ␤ yy and ␤ xx Ӎ ␤ yy . The average PPyV permittivity ␤ av is 2.10 ͑compared to 2.15 for PPV͒.…”
Section: B Electric Field Responsementioning
confidence: 99%
“…However, despite these results, no comprehensive study is available concerning the dynamical properties of the materials, especially the dynamical anisotropy. Realistic firstprinciples calculations are a way forward but they are computationally very demanding and it is often the case that the calculations of the dynamical properties are of the average axial values for simple polymers only, 16,17 while ignoring the anisotropy information. Nevertheless, some progress has been made in understanding the anisotropy of the polarizability for molecules and molecular crystals [18][19][20][21] and for the dielectric and vibrational properties of some of the simpler amino acid molecules.…”
Section: Introductionmentioning
confidence: 99%
“…28 However, to obtain results in good agreement with experiment, an empirical prefactor had to be used. Later van Faassen et al 19,20 showed that the inclusion of the VK functional in TDDFT calculations yields greatly improved polarizabilities for -conjugated polymers, obtaining results that are comparable to MP2 values. These results were indications that the VK formalism is a very promising one, even when it is applied to describe phenomena related to the particle-hole regime in systems of which the ground-state density nor the induced current density is slowly varying.…”
mentioning
confidence: 99%
“…16 Third, to describe nonlocal exchange-correlation effects in large systems, 15,17,18 it can be more convenient and more efficient to use a local functional of the current density instead of a nonlocal functional of the density. [19][20][21] Within TDDFT, one would need an exchange-correlation functional that is completely nonlocal to be able to take into account the charges that are induced at the surface of the system caused by the external field and that produce a counteracting field. 13,22 Instead, by applying a local functional of the current density, we can still take into account nonlocal effects that are induced in the system by an external field.…”
Section: Introductionmentioning
confidence: 99%